Igneous Rock Associations 1. Styles and Mechanisms of Caldera Collapse - Kennedy, Ben; Stix, John (Geoscience Canada, 2003)
Summary In this article, we summarize some of the most influential papers and concepts regarding caldera collapse. We also present a synopsis of the different types of calderas, their characteristics and field examples and provide a glossary of related nomenclature. We discuss piston,downsag, trapdoor, concentric step-down, chaotic, rifted and piece mealcalderas. Some calderas appear to be combinations of different types. We examine the complex interactions of variables that control the structure and morphology of calder as and result in a particular collapse style.